Transmission rate Optimization by dynamic resource allocation algorithm for RF/VLC heterogeneous networks - Gao, Ruimin; Wang, Ping; Wang, Jingyu; Yang, Ting; Shi, Huili; Wang, Zhao; Chi, Sihui; Che, Hui; Guo, Lixin (Optics express, 2021)
In this work, a dynamic resource allocation (DRA) algorithm is proposed to optimize the transmission rate subject to the access point assignment, bandwidth and transmit power allocation in RF/VLC heterogeneous networks, which combines the visible light communication (VLC) access point (AP) and radio frequency (RF) AP. To optimize the allocation among resource block (RB), subchannel and power, the time-average transmission rate is maximized under time-average transmit power budget. Specifically, the time-average optimization problem is converted into series of single timeslot online problem by Lyapunov optimization technique. Because of its complexity and non-convexity, the problem is decomposed into three independent subproblems for which a non-iterative solution is presented on the basis of Lagrange relaxation and convex optimization theory. Numerical simulations are conducted to demonstrate the effectiveness of the proposed DRA algorithm. And the comparisons with two classical algorithms are also given in terms of transmission rate and system stability. This work will benefit the design and development of hybrid RF/VLC system.